178 The Effect of Ophthalmic Surgery for Graves' Orbitopathy on Quality of Life – A Systematic Review and Meta-Analysis. (19th August 2022) - Woo, T; Li, C; Ganesananthan, S; Rajendram, R; Uddin, J; Lee, R; Dayan, C; Taylor, P
Abstract: Background: Graves' orbitopathy has a profound negative impact on quality of life. Surgery is undertaken to preserve vision, correct diplopia and improve aesthetics. We aimed to quantify the effect of different surgical approaches on quality of life. Method: Electronic databases were used from inception until 22nd March 2021 to identify studies assessing quality of life pre- and post-surgical intervention for Graves' orbitopathy. Two reviewers independently extracted data and performed quality assessments. Random-effects and Bayesian models for meta-analyses were utilised. Results: 10 articles comprising 632 patients were included. All used the Graves' Ophthalmopathy Quality of Life questionnaire (GO-QOL). For GO-QOL appearance, the pooled standardised mean improvement for patients after surgery was +0.72 (95% CI 0.50–0.94) I2=69% (95% CI 52–80%). For GO-QOL visual functioning, the pooled SMD for patients after surgery was +0.41 (95% CI 0.25–0.58) I2=60% (95% CI 36–74%). For visual appearance, orbital decompression yielded the greatest improvement (SMD+0.84, 95%CI 0.54–1.13) followed by eyelid surgery (SMD+0.38, 95% CI 0.05–0.70), while strabismus correction had no significant effect (SMD +0.94, 95% CI -0.10–1.99). Conversely strabismus correction was associated with the greatest improvement (SMD+1.25, 95%CI 0.29–2.21) in visual functioning, outperforming orbital decompression (SMD+0.29, 95%CI 0.15–0.43) and eyelid surgery (SMD+0.12, 95%CI -0.18–0.41). Conclusions: Ophthalmic surgery results in substantial improvements in quality of life in patients with Graves' orbitopathy, with greater perceived effects on appearance than visual function. Orbital decompression has particular impact on visual appearance, strabismus surgery may benefit both visual appearance and function equally whereas eyelid surgery benefits appearance alone.